PENGEMBANGAN BUKU BERBASIS MULTI REPRESENTASI SERI FLUIDA DENGAN PENDEKATAN SAINS TEKNOLOGI DAN MASYARAKAT (STM) - Kristin S Silaban; Fauzi Bakri; Mutia Delina (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
We have developed a multi-representative book for Fluids using Science Technology and Society approach. The content of this book represents in verbal, mathematic, graphic, and table forms. Fluids series book presented from basic knowledge to advanced knowledge. Research method that applied is Instructional Development Model (IDM) by Atwi Suparman with Educational research and development approach model consist of 9 stages. Legibility test has done to 5 students with result of content reach 81,25%, language 80%, and presentation 82,5%. This book has validated by content, media, and instructional expert team. The percentage result of proper content 80,19%, media 78,91%, and instructional 90,28%. From the validation result and test obtain very good interpretation, so that development of multi-representative book for fluids can be used to be reference book. Keywords: research development, multi-representative book, Fluids